A Conditional Mutation in SCD1 Reveals Linkage Between PIN Protein Trafficking, Auxin Transport, Gravitropism, and Lateral Root Initiation - Gibson, Carole L.; Isley, Jonathan W.; Falbel, Tanya G.; Mattox, Cassie T.; Lewis, Daniel R.; Metcalf, Kasee E.; Muday, Gloria K. (Frontiers in Plant Science, 2020)
Auxin is transported in plants with distinct polarity, defined by transport proteins of the PIN-formed (PIN) family. Components of the complex trafficking machinery responsible for polar PIN protein localization have been identified by genetic approaches, but severe developmental phenotypes of trafficking mutants complicate dissection of this pathway. We utilized a temperature sensitive allele of Arabidopsis thaliana SCD1 (stomatal cytokinesis defective1) that encodes a RAB-guanine nucleotide exchange factor. Auxin transport, lateral root initiation, asymmetric auxin-induced gene expression after gravitropic reorientation, and differential gravitropic growth were reduced in the roots of the scd1-1 mutant relative to wild type at the restrictive temperature of 25°C, but not at the permissive temperature of 18ºC. In scd1-1 at 25ºC, PIN1- and PIN2-GFP accumulated in endomembrane bodies. Transition of seedlings from 18ºC to 25°C for as little as 20 min resulted in the accumulation of PIN2-GFP in endomembranes, while gravitropism and root developmental defects were not detected until hours after transition to the nonpermissive temperature. The endomembrane compartments that accumulated PIN2-GFP in scd1-1 exhibited FM4-64 signal colocalized with ARA7 and ARA6 fluorescent marker proteins, consistent with PIN2 accumulation in the late or multivesicular endosome. These experiments illustrate the power of using a temperature sensitive mutation in the gene encoding SCD1 to study the trafficking of PIN2 between the endosome and the plasma membrane. Using the conditional feature of this mutation, we show that altered trafficking of PIN2 precedes altered auxin transport and defects in gravitropism and lateral root development in this mutant upon transition to the restrictive temperature.